Composite fiber material and preparation method, application, secondary battery and electrical device thereof

By using composite fiber materials to monitor the in-situ curing process in solid-state batteries, the problem of difficulty in monitoring in-situ curing in the prior art is solved, and the battery performance and safety is improved.

CN115839029BActive Publication Date: 2025-02-25CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210666130.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-14
Publication Date
2025-02-25
Estimated Expiration
2042-06-14

AI Technical Summary

Technical Problem

The prior art is difficult to effectively monitor the in-situ curing process of solid-state batteries, affecting battery performance and safety.

Method used

Composite fiber materials, including magnetic fiber cores and non-conductive polymer cladding, are used to monitor the in-situ curing process. The material produces magnetic changes under stress changes, converts magnetic signals into voltage signals, and monitors the in-situ curing reaction in real time.

Benefits of technology

Real-time monitoring of the in-situ curing process is realized, and optimized reference for curing parameters is provided, improving battery performance and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115839029B_ABST
    Figure CN115839029B_ABST
Patent Text Reader

Abstract

The present application relates to a composite fiber material and its preparation method, application, secondary battery, and electrical device. The composite fiber material includes a magnetic fiber core material and a first coating layer. The first coating layer is arranged on the surface of the magnetic fiber core material, and the material of the first coating layer is a non-conductive polymer. In the above-mentioned composite fiber material, the magnetic fiber core material thereof will change its magnetization state under stress, so the stress it is subjected to can be measured by its magnetic change. The first coating layer made of a non-conductive polymer is arranged on the surface of the magnetic fiber core material, which not only protects the magnetic fiber core material, but also facilitates the arrangement of the above-mentioned composite fiber material on the surface of the electrode assembly and melt-sealing it with the plastic sealing layer of the outer packaging to form an effective packaging structure; at the same time, it is also convenient for the above-mentioned composite fiber material to be drawn out from the outer packaging for connection with an external circuit to monitor the in-situ curing reaction during the preparation of the secondary battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a composite fiber material, a preparation method thereof, an application thereof, a secondary battery, and an electrical device. Background Art

[0002] Different from the commonly used lithium-ion batteries and lithium-ion polymer batteries, solid-state batteries are batteries that use solid electrodes and solid electrolytes. Since the solid electrolytes used in solid-state batteries are non-volatile and non-flammable, they are expected to fundamentally solve the safety issues of batteries. At the same time, since they can effectively inhibit lithium dendrites, all-solid-state batteries can further improve the energy density of lithium batteries, so they have become a current research hotspot.

[0003] Among the preparation methods of solid-state batteries, the in-situ curing method stands out due to its better ionic conductivity and better safety. Since in-situ curing is a polymer polymerization reaction, it is sensitive to temperature. It is generally carried out under the conditions of adding initiators such as isocyanic acid or isocyanate. The chain initiation process is relatively violent and there is an eruption process. The in-situ curing directly affects the interface performance of the solid-state battery, and ultimately affects the performance of the solid-state battery product. Therefore, how to monitor the in-situ curing process of preparing solid-state batteries is of great practical significance for product research and development. Summary of the invention

[0004] Based on this, it is necessary to provide a composite fiber material and a preparation method thereof that can monitor the in-situ curing process of solid-state batteries.

[0005] The present application also provides applications of the above-mentioned composite fiber material and secondary batteries, battery modules, battery packs and electrical devices.

[0006] The present application is implemented through the following technical solutions.

[0007] In a first aspect of the present application, a composite fiber material is provided, comprising:

[0008] Magnetic fiber core material; and

[0009] The first coating layer is arranged on the surface of the magnetic fiber core material, and the material of the first coating layer is a non-conductive polymer.

[0010] In some embodiments, the non-conductive polymer is at least one of polyethylene, polypropylene, polyethylene terephthalate, polybutylene terephthalate and polybutylene succinate;

[0011] And / or, the material of the magnetic fiber core material is at least one of cobalt-based magnetic fiber and iron-based magnetic fiber;

[0012] And / or, the outer diameter of the magnetic fiber core material is 5 μm-40 μm;

[0013] And / or, the thickness of the first coating layer is 1 μm-5 μm.

[0014] In some embodiments, the first coating layer includes a plurality of non-conductive polymer layers, and the plurality of non-conductive polymer layers are stacked on the surface of the magnetic fiber core material;

[0015] The materials in the non-conductive polymer layers are the same or different.

[0016] In some embodiments, the composite fiber material further comprises:

[0017] The second coating layer is provided between the magnetic fiber core material and the first coating layer, and the second coating layer contains a conductive material.

[0018] In some embodiments, the conductive material includes at least one of carbon nanotubes, carbon fibers and silver nanowires.

[0019] In some embodiments, the second coating layer further includes a substrate, and the conductive material is dispersed in the substrate.

[0020] In some embodiments, the substrate is a flexible substrate or a non-flexible substrate.

[0021] In some embodiments, the material of the flexible substrate includes at least one of polydimethylsiloxane, nitrile rubber and thermoplastic polyurethane;

[0022] The non-flexible substrate includes epoxy resin.

[0023] In a second aspect of the present application, a method for preparing a composite fiber material is provided, the method comprising the following steps:

[0024] The first coating layer is formed on the surface of the magnetic fiber core material.

[0025] The third aspect of the present application provides application of the above-mentioned composite fiber material in stress monitoring.

[0026] According to a fourth aspect of the present application, the composite fiber material is used as a stress sensor.

[0027] In a fifth aspect of the present application, a stress monitoring method is provided, using the composite fiber material of the first aspect of the present application, the method comprising the following steps:

[0028] Acquiring a magnetic change signal generated by the composite fiber material as the stress of the object to be tested changes;

[0029] The magnetic change signal is converted into a voltage signal to obtain the relationship between voltage and stress change.

[0030] A sixth aspect of the present application provides a stress monitoring system, comprising the composite fiber material and a data processing device according to the first aspect of the present application;

[0031] The composite fiber material is used to act on the object to be tested and generate a magnetic change signal as the stress of the object to be tested changes;

[0032] The data processing device is used to obtain the magnetic change signal, and convert the magnetic change signal into a voltage signal to obtain the relationship between voltage and stress change.

[0033] In the seventh aspect of the present application, a secondary battery is provided, comprising an outer package, an electrode assembly and the composite fiber material described in any one of the above items, wherein the electrode assembly and the composite fiber material are arranged in the outer package, and the composite fiber material is attached to the outer surface of the electrode assembly and led out from the outer package.

[0034] In some of the embodiments, the outer package has a plastic sealing layer, the plastic sealing layer is arranged toward the electrode assembly, and the plastic sealing layer and the first coating layer are melted together or can be melted together in the packaging step.

[0035] In some embodiments, the composite fiber material is distributed in a meandering manner on the outer surface of the electrode assembly.

[0036] In an eighth aspect of the present application, a method for preparing a secondary battery is provided, comprising the following steps:

[0037] attaching any of the above-mentioned composite fiber materials to the outer surface of an electrode assembly without electrolyte;

[0038] Placing the electrode assembly with the composite fiber material attached thereto in an outer package;

[0039] A liquid electrolyte containing an initiator is injected into the electrode assembly and the liquid electrolyte is allowed to undergo an in-situ curing reaction in the electrode assembly. The composite fiber material is used to monitor the in-situ curing reaction.

[0040] A ninth aspect of the present application provides a battery module comprising the secondary battery of the seventh aspect of the present application.

[0041] The tenth aspect of the present application provides a battery pack, comprising the battery module of the ninth aspect of the present application.

[0042] In the eleventh aspect of the present application, there is provided an electrical device comprising at least one selected from the secondary battery of the seventh aspect of the present application, the battery module of the ninth aspect of the present application, and the battery pack of the tenth aspect of the present application.

[0043] In the composite fiber material, the magnetic fiber core material changes its magnetization state under stress, so the stress it is subjected to can be measured by its magnetic change. A first coating layer made of a non-conductive polymer is arranged on the surface of the magnetic fiber core material, which not only protects the magnetic fiber core material, but also facilitates the arrangement of the composite fiber material on the surface of the electrode assembly and melt-encapsulation with the plastic sealing layer of the outer package to form an effective packaging structure; at the same time, it is also convenient for the composite fiber material to be drawn out from the outer package for connection with an external circuit to monitor the in-situ curing reaction during the preparation of the secondary battery.

[0044] As the in-situ curing reaction proceeds, the degree of crosslinking increases, and the liquid electrolyte containing the initiator gradually transforms from liquid to solid, thereby causing the surface of the electrode assembly to be subjected to tensile strain, such as slight bending. The composite fiber material provided in the electrode assembly exhibits magnetic changes with the tensile strain, so the in-situ curing reaction process can be monitored by monitoring the magnetic changes of the composite fiber material, thereby providing an important reference basis for optimizing the curing parameters of the in-situ curing reaction. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 is a schematic diagram of a secondary battery according to one embodiment of the present application.

[0046] Figure 2 yes Figure 1 An exploded view of a secondary battery according to an embodiment of the present application is shown.

[0047] Figure 3 It is a schematic cross-sectional view of a composite fiber material according to one embodiment of the present application.

[0048] Figure 4 It is a schematic diagram of a battery module according to one embodiment of the present application.

[0049] Figure 5 It is a schematic diagram of a battery pack according to one embodiment of the present application.

[0050] Figure 6 yes Figure 5 An exploded view of a battery pack according to an embodiment of the present application is shown.

[0051] Figure 7 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.

[0052] Description of reference numerals:

[0053] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 cover plate; 6, electrical device; 7 composite fiber material; 71 magnetic fiber core material; 72 first coating layer; 73 second coating layer. DETAILED DESCRIPTION

[0054] Below, the composite fiber material and its preparation method, application, secondary battery, battery module, battery pack and electric device of the present application are described in detail with appropriate reference to the drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0055] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0056] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0057] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0058] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0059] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0060] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0061] The term "and / or" as used herein includes any and all combinations of one or more related listed items. In the description of the present application, it should be understood that the terms "first" and "second" are used for descriptive purposes only and are not to be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the feature. In the description of the present application, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0062] Secondary battery

[0063] A secondary battery is a battery that can be recharged to activate the active materials after being discharged and continue to be used.

[0064] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0065] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 1 The secondary battery 5 is a square structure as an example.

[0066] In some embodiments, the secondary battery further includes an outer package, and the material of the soft package may also be an aluminum-plastic film. The aluminum-plastic film includes an aluminum foil and a plastic sealing layer and a protective layer disposed on opposite sides of the aluminum foil, wherein the plastic sealing layer is disposed toward the battery cell it encapsulates.

[0067] Furthermore, the material of the plastic layer can be at least one of polyethylene (PE), polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PET) and polybutylene succinate (PBS), which is used as the inner layer to seal and bond. The aluminum foil of the middle layer can prevent the infiltration of water vapor outside the battery and prevent the leakage of the internal electrolyte. The protective layer arranged on the outer layer mostly adopts polyester or nylon material with high melting point, which has strong mechanical properties, prevents the damage of external force to the secondary battery, and plays a role in protecting the battery.

[0068] In some embodiments, reference Figure 2 The outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity.

[0069] Further, refer to Figure 2 The electrode assembly 52 includes a stacked positive electrode sheet, a separator and a negative electrode sheet. The electrode assembly 52 can be formed by winding the positive electrode sheet, the negative electrode sheet and the separator through a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity of the outer package.

[0070] The number of the electrode assembly 52 included in the secondary battery 5 can be one or more, and those skilled in the art can select one according to specific practical needs.

[0071] In some examples, the secondary battery is a lithium-ion battery. In some examples, the secondary battery is a semi-solid battery or a solid-state battery.

[0072] Currently, for the research and development of solid-state batteries, due to the low ionic conductivity and the difficulty in improving the interface between solid electrolyte and metallic lithium, the semi-solid and quasi-solid-state routes are currently more widely used.

[0073] Generally, the in-situ curing method is to inject a liquid electrolyte containing an initiator into a battery cell containing a positive electrode sheet and a negative electrode sheet, fully infiltrate the positive electrode sheet and the negative electrode sheet, and then polymerize and cure the liquid electrolyte in situ on the surface of each layer and between the film layers, so as to obtain a semi-solid or solid-state battery. Furthermore, the above-mentioned liquid electrolyte contains electrolyte salts, solvents and initiators. In the in-situ curing, under the conditions of initiator and heating curing, the solvent reacts with the initiator to form a polymer, thereby converting the liquid electrolyte into a gel or solid electrolyte. However, there is currently no effective way to monitor the above-mentioned in-situ curing process.

[0074] Based on this, one embodiment of the present application provides a composite fiber material, including a magnetic fiber core material and a first coating layer. The first coating layer is arranged on the surface of the magnetic fiber core material. The material of the first coating layer is a non-conductive polymer.

[0075] In the composite fiber material, the magnetic fiber core material changes its magnetization state under stress, so the stress it is subjected to can be measured by its magnetic change. A first coating layer made of a non-conductive polymer is arranged on the surface of the magnetic fiber core material, which not only protects the magnetic fiber core material, but also facilitates the arrangement of the composite fiber material on the surface of the electrode assembly and melt-encapsulation with the plastic sealing layer of the outer package to form an effective packaging structure; at the same time, it is also convenient for the composite fiber material to be drawn out from the outer package for connection with an external circuit to monitor the in-situ curing reaction during the preparation of the secondary battery.

[0076] In such Figure 3 In the specific example shown, the composite fiber material 7 includes an internal magnetic fiber core material 71 and a first coating layer 72 coating the outer surface of the magnetic fiber core material 71 .

[0077] The secondary battery of the present application further includes the composite fiber material, which is attached to the outer surface of the electrode assembly and led out from the outer package.

[0078] Another embodiment of the present application further provides a method for preparing the secondary battery, comprising the following steps S11 to S14.

[0079] Step S11, attaching the composite fiber material to the outer surface of an electrode assembly that does not contain an electrolyte.

[0080] Step S12: placing the electrode assembly with the composite fiber material in an outer package.

[0081] Step S13, injecting a liquid electrolyte containing an initiator into the electrode assembly and encapsulating the electrode assembly in an outer package.

[0082] Step S14, causing the liquid electrolyte containing the initiator to undergo an in-situ curing reaction in the electrode assembly; the composite fiber material is used to monitor the in-situ curing reaction.

[0083] Furthermore, the above-mentioned liquid electrolyte containing an initiator contains an electrolyte salt, a solvent and an initiator. During in-situ curing, under the conditions of the initiator and heating curing, the solvent reacts with the initiator to form a polymer, thereby converting the liquid electrolyte into a gel or solid electrolyte.

[0084] In some embodiments, the electrolyte salt in the above-mentioned liquid electrolyte can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate and lithium tetrafluorooxalatophosphate.

[0085] In some embodiments, the solvent in the liquid electrolyte may be selected from at least one of ethylene carbonate (EC), vinylene carbonate (VC) and 1,3-dioxolane (DOL). Further, the initiator may be cyanic acid and cyanate. The solvent may undergo polymerization reaction under the action of the initiator to form a polymer.

[0086] As the in-situ curing reaction proceeds, the degree of crosslinking increases, and the liquid electrolyte gradually transforms from liquid to solid, causing the surface of the electrode assembly to be subjected to tensile strain, such as slight bending. The composite fiber material provided in the electrode assembly exhibits magnetic changes with the tensile strain, so the in-situ curing reaction process can be monitored by monitoring the magnetic changes of the composite fiber material, thereby providing an important reference basis for optimizing the curing parameters of the in-situ curing reaction.

[0087] Among them, the curing parameters include the type and amount of initiator, curing temperature and degree of cross-linking.

[0088] Furthermore, the composite fiber material is distributed in a meandering manner on the outer surface of the electrode assembly. Furthermore, each electrode assembly is provided with the composite fiber material alone, or some electrode assemblies in the secondary battery, for example, one is selected to provide the composite fiber material. Preferably, the composite fiber material is provided on an electrode assembly adjacent to the outer packaging or having a larger contact area in the secondary battery, such as an electrode assembly located at the edge of the secondary battery, so as to facilitate the effective packaging of the composite fiber material and the outer packaging.

[0089] Furthermore, the packaging in the above step S13 can be performed by packaging equipment.

[0090] Further, the outer diameter of the magnetic fiber core material is 5 μm-40 μm. The outer diameter of the magnetic fiber core material is preferably within the given range, which can simultaneously ensure the magnetic induction ability of the magnetic fiber core material, while not being too large to affect the battery packaging thickness and battery packaging performance. Further, the length of the magnetic fiber core material is 200-500 mm.

[0091] Furthermore, the material of the magnetic fiber core includes at least one of cobalt-based magnetic fiber and iron-based magnetic fiber.

[0092] Furthermore, the thickness of the first coating layer is 1 μm-5 μm. The thickness of the first coating layer is preferably within the given range, which can make the first coating layer easily melted in the package and ensure the tightness of the package to reduce leakage.

[0093] In some embodiments, in the composite fiber material, the non-conductive polymer is at least one of polyethylene, polypropylene and polyethylene terephthalate. The non-conductive polymer is selected from a given type of material, which can be well melted with the plastic sealing layer of the outer packaging, and then can be well melted in the packaging step of the above step S13, achieving effective packaging without air leakage and liquid leakage; at the same time, it can also facilitate the composite fiber material to be drawn out from the outer packaging, and realize the monitoring of the in-situ curing reaction.

[0094] Furthermore, the packaging temperature is 160-180° C. At this temperature, the plastic sealing layer of the outer packaging and the first coating layer of the composite fiber material can melt each other. It can be understood that the specific packaging temperature can be adjusted according to the materials of the plastic sealing layer of the outer packaging and the first coating layer.

[0095] Furthermore, the material of the first coating layer may be the same as or different from the material of the plastic sealing layer of the outer package, preferably the same.

[0096] In some embodiments, in the composite fiber material, the first coating layer includes a plurality of non-conductive polymer layers, and the plurality of non-conductive polymer layers are stacked on the surface of the magnetic fiber core material. Furthermore, the materials of the non-conductive polymer layers are the same or different.

[0097] For example, in some examples, the first covering layer is a PE layer, a PP layer, or a PET layer; in other examples, the first covering layer is a stack of at least two of the PE layer, the PP layer, and the PET layer.

[0098] The first coating layer can be formed by conventional methods in the art, such as solution polymerization, vapor deposition, and the like.

[0099] In some embodiments, the composite fiber material further includes a second coating layer. The second coating layer is disposed between the magnetic fiber core material and the first coating layer, and the second coating layer contains a conductive material. The second coating layer can eliminate the effect of the internal magnetic field, which is beneficial to improving the sensitivity of the composite fiber material to stress changes. Figure 3 In the specific example shown, the composite fiber material 7 further includes a second covering layer 73 covering the outer surface of the first covering layer 72 .

[0100] Furthermore, the conductive material in the second coating layer includes at least one of carbon nanotubes, carbon fibers and silver nanowires. The carbon nanotubes may be single-walled carbon nanotubes or multi-walled carbon nanotubes.

[0101] Furthermore, the second coating layer is a conductive material layer.

[0102] Furthermore, the thickness of the second coating layer is 100nm-500nm.

[0103] The second coating layer can be formed by electroplating, in-situ growth, coating, etc.

[0104] In some of the embodiments, the second coating layer in the composite fiber material may further include a substrate, and the conductive material is dispersed in the substrate.

[0105] Furthermore, the substrate is a flexible substrate or a non-flexible substrate.

[0106] The material of the flexible substrate includes at least one of polydimethylsiloxane, nitrile rubber and thermoplastic polyurethane. These flexible substrates have good tensile properties and flexibility, and can adapt well to stress changes, so the response sensitivity of the composite fiber material to stress changes can be improved.

[0107] Non-flexible substrates include epoxy resins and the like.

[0108] The second coating layer containing the substrate can be prepared by the following method: the substrate and the conductive material are compounded with the magnetic fiber core material by melting to form the second coating layer on the surface of the magnetic fiber core material. Furthermore, the temperature of the melt compounding can be adjusted according to the type of the substrate. For example, it can be carried out at 100-300°C.

[0109] As mentioned above, one embodiment of the present application further provides an application of the above-mentioned composite fiber material in stress monitoring.

[0110] Furthermore, the composite fiber material is placed on the object to be tested to monitor the stress change of the object to be tested. That is, the composite fiber material can be used as a stress sensor. The stress monitoring method using the composite fiber material includes the following steps S21 to S22.

[0111] Step S21 : obtaining a magnetic change signal generated by the composite fiber material as the stress of the object to be tested changes.

[0112] Step S22: convert the magnetic change signal into a voltage signal, and then obtain the relationship between voltage and stress change.

[0113] In this way, according to the relationship between the voltage and the stress change, the stress change of the object to be measured can be monitored.

[0114] An embodiment of the present application further provides a stress monitoring system using the composite fiber material, comprising the composite fiber material and a data processing device.

[0115] The composite fiber material is used to act on the object to be measured and generate a magnetic change signal as the stress of the object to be measured changes.

[0116] The data processing device is used to obtain the magnetic change signal, and convert the magnetic change signal into a voltage signal to obtain the relationship between voltage and stress change.

[0117] Positive electrode

[0118] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material.

[0119] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0120] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0121] In some embodiments, the positive electrode active material may adopt a positive electrode active material for a battery that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO 2) , lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM523), LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM211), LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM811), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0122] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0123] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0124] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0125] Negative electrode

[0126] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.

[0127] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0128] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0129] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0130] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0131] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0132] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0133] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0134] Isolation film

[0135] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0136] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0137] Figure 4 4 is an example of a battery module. Figure 4 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.

[0138] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0139] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.

[0140] Figure 5 and Figure 6 1 is a battery pack 1 as an example. Figure 5 and Figure 6 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0141] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited to these.

[0142] As the electrical device, a secondary battery, a battery module or a battery pack may be selected according to its usage requirements.

[0143] Figure 7 The power consumption device 6 is used as an example. The power consumption device 6 is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the power consumption device's requirements for high power and high energy density of secondary batteries, a battery pack or a battery module can be used.

[0144] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.

[0145] In order to make the purpose, technical solutions and advantages of the present application more concise and clear, the present application is described with the following specific embodiments, but the present application is by no means limited to these embodiments. The embodiments described below are only preferred embodiments of the present application and can be used to describe the present application, and cannot be understood as limiting the scope of the present application. It should be pointed out that any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

[0146] In order to better illustrate the present application, the present application is further described below in conjunction with the embodiments. The following are specific embodiments.

[0147] (I) Preparation of composite fiber materials

[0148] Example 1

[0149] (1) Magnetic fiber core material: The material is cobalt-based magnetic fiber, which is a drawn wire made of cobalt-based magnetic fiber by metal drawing.

[0150] (2) Forming a second coating layer: electroplating a single-walled carbon nanotube layer on the outer surface of the magnetic fiber core material.

[0151] (3) Forming the first coating layer: depositing a PP layer on the carbon nanotube layer by CVD to obtain a composite fiber material.

[0152] Example 2

[0153] (1) Magnetic fiber core material: The material is cobalt-based magnetic fiber, which is a drawn wire made of cobalt-based magnetic fiber by metal drawing.

[0154] (2) Forming a second coating layer: The nitrile rubber, the magnetic fiber core material and the conductive material (single-walled carbon nanotube) are melt-compounded at 200° C. and subjected to wire drawing to obtain a magnetic fiber core material coated with a second coating layer.

[0155] (3) Forming a first coating layer: a PP layer is plated on the surface of the second coating layer of the magnetic fiber core material by vacuum evaporation to obtain a composite fiber material.

[0156] Example 3

[0157] (1) Magnetic fiber core material: The material is cobalt-based magnetic fiber, which is a drawn wire made of cobalt-based magnetic fiber by metal drawing.

[0158] (2) Forming a second coating layer: The nitrile rubber, the magnetic fiber core material and the conductive material (AgNWS nanowire) are melt-compounded at 250° C. and subjected to wire drawing to obtain a magnetic fiber core material coated with a second coating layer.

[0159] (3) Forming a first coating layer: a PP layer is plated on the surface of the second coating layer of the magnetic fiber core material by vacuum evaporation to obtain a composite fiber material.

[0160] (II) Semi-solid battery production is as follows:

[0161] (1) The positive electrode slurry is coated on a 10 μm thick aluminum foil and pressed to obtain a positive electrode sheet; the positive electrode slurry is NCM98: SP: SWCNT: PVDF = 98%: 0.6%: 0.2%: 1.2%; the slurry viscosity is 7500 mpa·s, and the solid content is 68%.

[0162] (2) The negative electrode slurry is coated on a 4.5 μm thick copper foil and pressed to obtain a negative electrode sheet; the negative electrode slurry is SiO: graphite: SP: SWCNT: PAALi = 48.4%: 48.4%: 1.04%: 0.06%: 2.1%. (The gram capacity of silicon dioxide and graphite mixed is 1250 mAh / g).

[0163] (3) Assembling the negative electrode sheet, the positive electrode sheet and the separator to form an electrode assembly, and embedding the composite fiber material prepared in the above embodiments in the edge and each surface of the electrode assembly in a winding manner, and finally leading out to obtain an electrode assembly with the above composite fiber material built in.

[0164] (5) Injecting a liquid electrolyte containing an initiator into the electrode assembly. The liquid electrolyte containing an initiator comprises ethylene carbonate and ethyl methyl carbonate in a mass ratio of 3:7, further comprising LiPF6 at a concentration of 1 mol / L, and further comprising isocyanic acid and isocyanate accounting for 0.5% of the total mass of ethylene carbonate and ethyl methyl carbonate.

[0165] (6) The electrode assembly is encapsulated with an aluminum-plastic film (composed of a laminated nylon layer, an Al layer, and a PP layer) and the encapsulation is performed at 150°C.

[0166] (7) The packaged battery is slowly heated up so that the injected semi-solid electrolyte undergoes an in-situ curing reaction under the presence of a chain initiator. The composite fiber material is used as a stress sensor to monitor the curing process. A certain voltage and stress-strain curve are output by an external data processing device connected to the composite fiber material to monitor the tensile strain process. The curing start process, the degree of cross-linking, and the state after curing can be obtained.

[0167] (8) After the in-situ cured battery is left standing at high temperature, the capacity splitting operation is performed. A solid-state secondary battery is obtained. The first efficiency and medium voltage are recorded. The specific steps of capacity splitting are: the battery after high temperature standing is left standing for t1, and then charged to U1 at a constant current of 0.02C, and then discharged to U2 at a constant current of 0.1C, and then charged to U2 at a constant voltage of 0.02C, and stood for t2, and discharged to U3 at a constant current of 0.1C, and then decompressed and sealed, and the capacity splitting is completed; t1 is 12h, U1 is 3.5V, U2 is 4.6V, U3 is 2.5V, and t2 is 3min.

[0168] Some parameters of each embodiment are shown in Table 1. At the same time, the maximum expansion rate of the radial dimension of the composite fiber material during the tensile strain process monitored in the above step (7) is recorded. The maximum expansion rate is the ratio of the maximum radial dimension of the composite fiber material after expansion during the tensile strain process to the original radial dimension.

[0169] The resistance change rate means the ratio of the resistance of the composite fiber material at the maximum radial dimension after expansion during the tensile strain process to the original resistance before expansion.

[0170] Table 1

[0171]

[0172] It can be seen from the maximum expansion rate and resistance change rate of each embodiment that the corresponding composite fiber material has good response sensitivity to stress changes.

[0173] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0174] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims, and the description and drawings may be used to interpret the contents of the claims.

Claims

1. A secondary battery, characterized in that: It comprises an outer package, an electrode assembly and a composite fiber material, wherein the electrode assembly and the composite fiber material are arranged in the outer package, and the composite fiber material is attached to the outer surface of the electrode assembly and led out from the outer package; The composite fiber material comprises a magnetic fiber core material and a first coating layer, wherein the first coating layer is arranged on the surface of the magnetic fiber core material, and the material of the first coating layer is a non-conductive polymer; The secondary battery also includes a gel electrolyte or a solid electrolyte formed by an in-situ curing reaction in the electrode assembly; the composite fiber material is used to generate a magnetic change signal as the stress of the electrode assembly changes during the in-situ curing reaction.

2. The secondary battery according to claim 1, wherein: The non-conductive polymer is at least one of polyethylene, polypropylene, polyethylene terephthalate, polybutylene terephthalate and polybutylene succinate; And / or, the material of the magnetic fiber core material is at least one of cobalt-based magnetic fiber and iron-based magnetic fiber; And / or, the outer diameter of the magnetic fiber core material is 5 μm-40 μm; And / or, the thickness of the first coating layer is 1 μm-5 μm.

3. The secondary battery according to claim 1, wherein: The first coating layer includes a plurality of non-conductive polymer layers, and the plurality of non-conductive polymer layers are stacked on the surface of the magnetic fiber core material; The materials in each of the non-conductive polymer layers are the same or different.

4. The secondary battery according to any one of claims 1 to 3, characterized in that: The composite fiber material also includes: The second coating layer is provided between the magnetic fiber core material and the first coating layer, and the second coating layer contains a conductive material.

5. The secondary battery according to claim 4, characterized in that: The conductive material includes at least one of carbon nanotubes, carbon fibers and silver nanowires.

6. The secondary battery according to claim 4, characterized in that: The second coating layer also includes a substrate, and the conductive material is dispersed in the substrate.

7. The secondary battery according to claim 6, characterized in that: The substrate is a flexible substrate or a non-flexible substrate.

8. The secondary battery according to claim 7, characterized in that The material of the flexible substrate includes at least one of polydimethylsiloxane, nitrile rubber and thermoplastic polyurethane; The non-flexible substrate includes epoxy resin.

9. The secondary battery according to any one of claims 1 to 3, characterized in that: The outer package has a plastic sealing layer, the plastic sealing layer is arranged toward the electrode assembly, and the plastic sealing layer and the first coating layer are fused to each other or can be fused to each other in the packaging step.

10. The secondary battery according to any one of claims 1 to 3, characterized in that: The composite fiber material is distributed on the outer surface of the electrode assembly in a meandering manner.

11. A secondary battery stress monitoring method, characterized in that: Using the secondary battery as claimed in any one of claims 1 to 10; The stress monitoring method comprises the following steps: Acquiring a magnetic change signal of the composite fiber material generated by a stress change of the electrode assembly during the in-situ curing reaction; The magnetic change signal is converted into a voltage signal to obtain the relationship between voltage and stress change.

12. A secondary battery stress monitoring system, characterized in that: A device comprising a secondary battery and a data processing device as claimed in any one of claims 1 to 10; The data processing device is used to obtain a magnetic change signal generated by the stress change of the electrode assembly, and convert the magnetic change signal into a voltage signal to obtain a relationship between voltage and stress change.

13. A method for preparing a secondary battery, characterized in that: The steps include: The composite fiber material is attached to the outer surface of the electrode assembly without electrolyte; the composite fiber material comprises a magnetic fiber core material and a first coating layer, the first coating layer is arranged on the surface of the magnetic fiber core material, and the material of the first coating layer is a non-conductive polymer; Placing the electrode assembly with the composite fiber material attached thereto in an outer package and leading it out from the outer package; A liquid electrolyte containing an initiator is injected into the electrode assembly and the liquid electrolyte undergoes an in-situ curing reaction in the electrode assembly to form a gel electrolyte or a solid electrolyte. The composite fiber material is used to monitor the in-situ curing reaction and generate a magnetic change signal as the stress of the electrode assembly changes during the in-situ curing reaction.

14. A battery module, characterized in that: The invention comprises the secondary battery according to any one of claims 1 to 10.

15. A battery pack, characterized in that: Comprising the battery module as claimed in claim 14.

16. An electrical device, characterized in that: The battery comprises at least one selected from the group consisting of the secondary battery according to any one of claims 1 to 10, the battery module according to claim 14, and the battery pack according to claim 15.

Citation Information

Patent Citations

  • Micro-nano magnetic fiber and preparation method of micro-nano magnetic fiber

    CN111663198A